A 79GHz Adaptive Gain Low Noise Amplifier for Radar Receivers - Manjula, J; Ruhan Bevi, A (International Journal of Engineering and Technology, 2018)
This paper presents an Adaptive Gain 79GHz Low Noise Amplifier (LNA) suitable for Radars applications. The circuit schematic is a two stage LNA consists of Differential cascode configuration followed by a simple common source amplifier with an Adaptive Biasing (ADB) circuit. Adaptive biasing is a three- stage common source amplifier to decrease output voltage as input power increases. The circuit is simulated in 180nm CMOS technology and the simulation results have proved that the circuit operates at the center frequency 79GHz with adaptive biasing for adaptive gain. The gain analysis shows a decrease of 35-30dB with an increase in input power -50 to 0 dB. At 79GHz the circuit has achieved the input reflection coefficient (S11) of -24.7dB, reverse isolation (S12) of -3 dB, forward transmission coefficient (S21) of -2.97dB and output reflection coefficient (S22) of -5.62 dB with the reduced noise figure of 0.9 dB and a power consumption of 236 mW.Â Â